Yarn diameter and linear mass correlation - Carvalho, Vítor (2009)
This paper focuses on the determination of the statistical correlation between yarn diameter and yarn linear mass. The experimental methods employed are based on optical analysis and on image processing techniques applied to electron microscope image. several different cotton yarns were examined over a wide range of yarn linear masses. the results indicate that diameter predicted by the relationship commonly quatode in literature can be as much as 62% smaller than those experimentally observed.